2019
DOI: 10.1111/pedi.12870
|View full text |Cite
|
Sign up to set email alerts
|

Identification of infants with increased type 1 diabetes genetic risk for enrollment into Primary Prevention Trials—GPPAD‐02 study design and first results

Abstract: Primary prevention of type 1 diabetes (T1D) requires intervention in genetically at‐risk infants. The Global Platform for the Prevention of Autoimmune Diabetes (GPPAD) has established a screening program, GPPAD‐02, that identifies infants with a genetic high risk of T1D, enrolls these into primary prevention trials, and follows the children for beta‐cell autoantibodies and diabetes. Genetic testing is offered either at delivery, together with the regular newborn testing, or at a newborn health care visits befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 13 publications
0
34
0
1
Order By: Relevance
“…Identification of genetic loci using hypothesis-free genome wide association studies (GWAS) has given novel insights into diseases 4e6 , identified potential drug targets 7 , and led to the use of polygenic risk scores in selecting individuals for clinical trials 8 . However, until recently, identification of OA loci was trailing behind other complex diseases and phenotypes such as rheumatoid arthritis (over 100 risk loci; 9 ) and height (over 3,000 loci; 10 ), with only 19 OA loci reported up to April 2017 at genome wide significance level of P 5 Â 10 À8 (Fig.…”
Section: Identification Of New Oa Genetic Risk Locimentioning
confidence: 99%
“…Identification of genetic loci using hypothesis-free genome wide association studies (GWAS) has given novel insights into diseases 4e6 , identified potential drug targets 7 , and led to the use of polygenic risk scores in selecting individuals for clinical trials 8 . However, until recently, identification of OA loci was trailing behind other complex diseases and phenotypes such as rheumatoid arthritis (over 100 risk loci; 9 ) and height (over 3,000 loci; 10 ), with only 19 OA loci reported up to April 2017 at genome wide significance level of P 5 Â 10 À8 (Fig.…”
Section: Identification Of New Oa Genetic Risk Locimentioning
confidence: 99%
“…It is likely that population screening will use a combination of genetics with emergent risk factor testing to determine those eligible for intervention (e.g. intervention trials prior to disease onset, such as with oral insulin therapy) and is being tested now [47]. With the ever-expanding reliance on the merger of electronic health records with biobanks, these research directions could be directly applied to prediction, intervention and treatment in diverse and previously underserved populations.…”
Section: From Bench To Bedside To Communitymentioning
confidence: 99%
“…Eine Risikostratifizierung ermöglicht es, Kinder mit einem gegenüber der Allgemeinbevölkerung 25-fach höheren Risiko eines Frühstadiums oder manifesten Diabetes bereits im Kleinkindalter zu ermitteln. Die betroffenen Familien werden zum Diabetesrisiko beraten, und die Teilnahme an einer Primärpräventionsstudie mit oralem Insulin wird angeboten [ 35 ].…”
Section: Genetisches Risikoscreening Und Primärpräventionunclassified